Emotion Avoidance in Patients with Anorexia Nervosa: Initial Test of a Functional Model - Wildes, Jennifer E. (2010)
OBJECTIVE: This study aimed to evaluate emotion avoidance in patients with anorexia nervosa (AN) and to examine whether emotion avoidance helps to explain (i.e., mediates) the relation between depressive and anxiety symptoms and eating disorder (ED) psychopathology in this group. METHOD: Seventy-five AN patients completed questionnaires to assess study variables. Rates of emotion avoidance were compared to published data, and regression models were used to test the hypothesis that emotion avoidance mediates the relation between depressive and anxiety symptoms and ED psychopathology in AN. RESULTS: AN patients endorsed levels of emotion avoidance that were comparable to or higher than other psychiatric populations and exceeded community controls. As predicted, emotion avoidance significantly explained the relations of depressive and anxiety symptoms to ED psychopathology. DISCUSSION: Findings confirm that emotion avoidance is present in patients with AN and provide initial support for the idea that anorexic symptoms function, in part, to help individuals avoid aversive emotional states.